2023
DOI: 10.1007/s40820-023-01037-1
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functional Lithiophilic/Sulfiphilic Binary-Metal Selenide Quantum Dots Toward High-Performance Li–S Full Batteries

Abstract: The commercial viability of lithium–sulfur batteries is still challenged by the notorious lithium polysulfides (LiPSs) shuttle effect on the sulfur cathode and uncontrollable Li dendrites growth on the Li anode. Herein, a bi-service host with Co-Fe binary-metal selenide quantum dots embedded in three-dimensional inverse opal structured nitrogen-doped carbon skeleton (3DIO FCSe-QDs@NC) is elaborately designed for both sulfur cathode and Li metal anode. The highly dispersed FCSe-QDs with superb adsorptive-cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…These peaks can be attributed to the reduction of S 8 to highly soluble LiPSs, the reduction of Li 2 S 4 to insoluble species (Li 2 S 2 /Li 2 S), and the reverse process, respectively. , Furthermore, the S/Zn 0.12 MoS 2 -CNF-based cell exhibits lower reduction peak potential and higher oxidation peak potential. This can be attributed to the accelerated redox kinetics of polysulfides on S/Zn 0.12 MoS 2 -CNFs, which effectively reduces electrochemical polarization . The CV curves of S/Zn 0.12 MoS 2 -CNFs, S/MoS 2 -CNFs, and S/CNFs batteries were analyzed, and the curve slopes of the redox peaks were fitted, as shown in Figure S21.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks can be attributed to the reduction of S 8 to highly soluble LiPSs, the reduction of Li 2 S 4 to insoluble species (Li 2 S 2 /Li 2 S), and the reverse process, respectively. , Furthermore, the S/Zn 0.12 MoS 2 -CNF-based cell exhibits lower reduction peak potential and higher oxidation peak potential. This can be attributed to the accelerated redox kinetics of polysulfides on S/Zn 0.12 MoS 2 -CNFs, which effectively reduces electrochemical polarization . The CV curves of S/Zn 0.12 MoS 2 -CNFs, S/MoS 2 -CNFs, and S/CNFs batteries were analyzed, and the curve slopes of the redox peaks were fitted, as shown in Figure S21.…”
Section: Results and Discussionmentioning
confidence: 99%
“…This can be attributed to the accelerated redox kinetics of polysulfides on S/Zn 0.12 MoS 2 -CNFs, which effectively reduces electrochemical polarization. 50 The CV curves of S/Zn 0.12 MoS 2 -CNFs, S/MoS 2 -CNFs, and S/CNFs batteries were analyzed, and the curve slopes of the redox peaks were fitted, as shown in Figure S21. It was found that the S/Zn 0.12 MoS 2 -CNFs had a greater slope, indicating that it had good catalytic reaction kinetics (Tables S1−3).…”
Section: Resultsmentioning
confidence: 99%
“…A comparison with recent research work also demonstrated the superior cyclic performance of the well-designed Li-N/CF@V 2 CT x anodes, surpassing most composite anodes and enabling ultrahigh current densities (Figure S17, Supporting Information). [52][53][54][55][56][57] In summary, the hierarchical 3D macropore structure with welldispersed lithiophilic V 2 CT x nanosheets effectively suppressed dendrite growth and volume fluctuation.…”
Section: Resultsmentioning
confidence: 99%
“…Benefiting from the physical confinement of the carbon substrate, the intrinsic shortcoming of S-based composites can be apparently enhanced. [96][97][98] Impressively, these micro-/nanostructured carbon materials will not only facilitate electrolyte penetration into electrode to boost zinc-ion diffusion kinetics, but also buffer the volume fluctuation of S cathode during the dynamic cycling. [99][100][101] A pioneering work was carried out by using carbon-nanotube-supported 50 wt% sulfur (generalized as S@CNT-50) as a conversional cathode, Jiang and co-workers designed a rechargeable and cost-effective aqueous Zn-S battery, as indicated in Figure 3a.…”
Section: Electrode Engineeringmentioning
confidence: 99%